Changes in mood instability, episode and symptom density among bipolar patients living under strict lockdown: insights from a third-world country with a never-ending quarantine - Samame, Cecilia (2022)
Introduction: During 2020, measures to contain the global health crisis caused by the coronavirus disease (COVID-19) included social confinement, with the consequent interruption of normal activities. In Argentina, particularly, the confinement was one of the longest and strictest in the world. Within this context, the current study was aimed at exploring changes in illness severity among bipolar disorder (BD) patients living under strict lockdown. Method: Ninety BD outpatients under naturalistic conditions were followed from March (when the lockdown measures were imposed in our country) to September 2020. Thirteen variables of illness severity were assessed during this period, which were compared with the results obtained during the same 28-week period of the previous year (i.e., from March to September 2019). Results: No significant differences were observed between periods in the rate of patients that remained euthymic during the entire follow-up (28.9% before the pandemic versus 41.1% during the pandemic, p = 0.09). For most variables, no significant differences were observed. A small decrease was found in depressive episode density (from 0.39 ± 0.74 to 0.22 ± 0.63, p = 0.003). Symptom and episode density during the pre-pandemic period and the number of previous depressive episodes at study entry predicted worse outcomes during the pandemic. Conclusion: Findings from a large sample of BD individuals indicate that illness severity variables have not worsened as a result of the lockdown. In addition, our findings suggest an important degree of positive coping among BD patients and emphasize the effectiveness of telepsychiatry in treating this clinical population.